دراﺳﺔ إﺣﺼﺎﺋﯿﺔ وﺻﻔﯿﺔ ﻟﻠﻘﯿﺎﺳﺎت اﻟﺠﺴﻤﯿﺔ ﻟﻺﻧﺎث (Journal of the College of Education for Women, 2019)
The research problem: the research problem which is the garments industry, as a whole it does not rely on a single system in the sizes of the clothing and the working companies, see that it is not plausible that the sizes be unificd and consistent in all companies . The current sizes in the domestic Iraqi markets are not suitable for some females ,on the other hand the Iraqi industry suffers the lack of a modern standard for some Iraqis female bodies. The Signifiance of the research: lies in the study of the diversity of the human body sizes and naming them to reflect the desires and requirements of the consumer and try to find a method to meet their expectations as well as to raise the level of garments industry supported by modern technology and then to the issuance of Iraqi fashion magazines.